El desarrollo Psicoactivo y su incidencia en el comportamiento de los adolescentes de la escuela de educación básica Babahoyo del circuito c05 de la cuidad de Babahoyo, provincia de los ríos - Vaca Chonillo, Andrea Fabiola (2015)
In the following final report of research is related to psycho-affective development and its incidence in adolescents of the campus and that affectivity, emotions, feelings and passions, play an important role in our lives. Emotions, feelings, etc. Now, the emotions, the passions ... can also be triggered in the moments that are fixed in the control of the same, they can leave our control and this can come to affect our psychological well-being or to repercutar in the others, of there the Need for proper affective education Adolescence is a stage of crisis and critical moments for human development, due to the series of physical and emotional changes of childhood, which in turn to puberty and highlight the complex between the body and the inner world La Person, changes change the adolescent into an identity crisis that faces them, the family demands and the society of producers great anxiety, anger and confusion